Considerations for patient selection for focal therapy. (December 2013) - Ward, John F.; Pisters, Louis L.
Focal therapy for prostate cancer is a nascent and emerging field. As such, the patient selection criteria for this new treatment paradigm are evolving in parallel to both the technology on which this approach depends and to our unfolding understanding of the natural history of prostate cancer. Until, and while, prospective trials of focal therapy are being reported, patient selection criteria will be flexible and very dependent on the therapeutic goals. We must carefully define the therapeutic intentions of focal therapy before engaging in the actual process of determining optimal patient selection. The therapeutic intent will define the most appropriate candidate for such therapy. Patient selection encompasses multiple complex issues including the type of prostate biopsy (12 core transrectal versus mapping transperineal) to the type of imaging (multiparametric magnetic resonance imaging or enhanced ultrasound) to the specific anatomical location of the disease within the prostate (apex, mid-prostate, base) and a comprehensive assessment of the patient's overall health and life expectancy. It is not as simple as saying a patient with a certain grade or a certain number of cores is or is not appropriate for focal therapy. There are many more considerations for a reasonable and thoughtful approach to this new treatment.